Is Caperatic Acid the Only Compound Responsible for Activity of Lichen Platismatia glauca within the Nervous System? - Elżbieta Studzińska-Sroka; Aleksandra Majchrzak-Celińska; Monika Bańdurska; Natalia Rosiak; Dominik Szwajgier; Ewa Baranowska-Wójcik; Marcin Szymański; Wojciech Gruszka; Judyta Cielecka-Piontek (MDPI AG, 2022)
Lichens are a source of various biologically active compounds. However, the knowledge about them is still scarce, and their use in medicine is limited. This study aimed to investigate the therapeutic potential of the lichen Platismatia glauca and its major metabolite caperatic acid in regard to their potential application in the treatment of central nervous system diseases, especially neurodegenerative diseases and brain tumours, such as glioblastoma. First, we performed the phytochemical analysis of the tested P. glauca extracts based on FT-IR derivative spectroscopic and gas chromatographic results. Next the antioxidant properties were determined, and moderate anti-radical activity, strong chelating properties of Cu2+ and Fe2+ ions, and a mild effect on the antioxidant enzymes of the tested extracts and caperatic acid were proved. Subsequently, the influence of the tested extracts and caperatic acid on cholinergic transmission was determined by in vitro and in silico studies confirming that inhibitory effect on butyrylcholinesterase is stronger than against acetylcholinesterase. We also confirmed the anti-inflammatory properties of P. glauca extracts and caperatic acid using a COX-2 and hyaluronidase inhibition models. Moreover, our studies show the cytotoxic and pro-apoptotic activity of the P. glauca extracts against T98G and U-138 MG glioblastoma multiforme cell lines. In conclusion, it is possible to assume that P. glauca extracts and especially caperatic acid can be regarded as the source of the valuable substances to finding new therapies of central nervous system diseases.